Robotic Exoskeleton for Young Adult Large-Lesion Stroke: A Case Report - Arisanti, Farida; Yunita Sari, Alfi; Sulistyo Wulandari, Maria Agustina; Larasati, Rinesa; Biben, Vitriana (Rifa'Institute, 2026)
Introduction: Large-lesion stroke in young adults often causes severe functional impairment, severely inhibiting people’s reintegration and long-term autonomy. In the subacute phase, severe motoric weakness, postural instability, and decreased aerobic capacity often inhibit effective walking rehabilitation. Objective: To evaluate the potential benefits of integrating a robotic dermoskeleton (KEEOGO) into the